2018
DOI: 10.1183/16000617.0057-2018
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiovascular disease and COPD: dangerous liaisons?

Abstract: Chronic obstructive pulmonary disease (COPD) and cardiovascular disease (CVD) frequently occur together and their coexistence is associated with worse outcomes than either condition alone. Pathophysiological links between COPD and CVD include lung hyperinflation, systemic inflammation and COPD exacerbations. COPD treatments may produce beneficial cardiovascular (CV) effects, such as long-acting bronchodilators, which are associated with improvements in arterial stiffness, pulmonary vasoconstriction, and cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
190
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(244 citation statements)
references
References 196 publications
1
190
0
15
Order By: Relevance
“…Third, some baseline information in the stable period was de cient, and usage of cardioprotective medications were not fully recorded, liker anti-platelet agents and statins, which might result in biases. [14,35] Fourth, baseline comorbidities were reported by patients themselves and not validated by detailed laboratory tests, which might had recall bias. Fifth, we did not take some useful scales of cardiovascular risk assessment into consideration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, some baseline information in the stable period was de cient, and usage of cardioprotective medications were not fully recorded, liker anti-platelet agents and statins, which might result in biases. [14,35] Fourth, baseline comorbidities were reported by patients themselves and not validated by detailed laboratory tests, which might had recall bias. Fifth, we did not take some useful scales of cardiovascular risk assessment into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional risk factors of CVDs might have warning effects, including previous history, hypertension, diabetes, hyperlipidemia and hyperuricemia. In addition, serious side effects of some drugs are chief culprits of CVEs, such as theophylline [14] and widely-concerned uoroquinolones [15]. Relationship between inhaled long-acting bronchodilators and CVDs is still highly debated, for their pharmacological mechanisms are contradictory to therapeutics of cardiac remodeling and heart failure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of treatment, all guidelines concur in recommending to care for these conditions as in the general population 9 . Importantly, COPD should not be considered as a contraindication to the use of selective beta-blockers when there is a clear cardiovascular indication (ischaemic heart disease, heart failure) 34 . Some observational studies suggested that drugs used in cardiovascular conditions could improve the prognosis of COPD (exacerbations occurrence, survival), even in the absence of cardiovascular disease or risk 35,36 .…”
Section: Comorbiditiesmentioning
confidence: 99%
“…The mechanisms that underlie the association between COPD and CVDs are not well understood, but several processes are thought to be important and may interact with each other. These include lung hyperinflation, hypoxaemia, pulmonary hypertension, systemic inflammation and oxidative stress, exacerbations, shared risk factors and shared genetics, as well as COPD phenotype (6). Endothelial dysfunction fundamentally contributes to the development of atherosclerosis that finally leads to coronary heart disease (CHD).…”
Section: Introductionmentioning
confidence: 99%